2018
DOI: 10.4103/jcd.jcd_14_18
|View full text |Cite
|
Sign up to set email alerts
|

“Evaluation of the antibacterial efficacy of EZLASE diode LASER on the infected root canal system:” An in vivo study

Abstract: Aims and Objectives:The aim of this in vivo study was to evaluate the antibacterial efficacy of a diode LASER on the infected root canal system.Methodology:A total of forty patients with infected root canals were selected. The root canals were prepared mechanically, and irrigation was done with 3% sodium hypochlorite (NaOCl). Microbiological samples were collected before LASER treatment with the help of the master apical file (MAF) to full working length for subsequent microbiological examination. The procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 16 publications
1
12
0
3
Order By: Relevance
“…The results showed that a combination of irrigation with NaOCl and laser irradiation is more effective than conventional endodontic therapy for a reduction in bacterial flora from the root canal system. 7 In 2014, Ashofteh et al performed a study on infected root canals to compare the antibacterial effect of intracanal irrigants and diode lasers. They used an 830 nm diode laser and output power of 1.5 W and a frequency of 20 Hz.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that a combination of irrigation with NaOCl and laser irradiation is more effective than conventional endodontic therapy for a reduction in bacterial flora from the root canal system. 7 In 2014, Ashofteh et al performed a study on infected root canals to compare the antibacterial effect of intracanal irrigants and diode lasers. They used an 830 nm diode laser and output power of 1.5 W and a frequency of 20 Hz.…”
Section: Discussionmentioning
confidence: 99%
“…5 To improve the efficacy of the root canal disinfection process many techniques have been used and lots of researches are still conducted to reach the quickest and most convenient way of achieving this goal. 6,7 Lasers have been introduced as a promising alternative to conventional chemical irrigation, in endodontics since a long time ago. 8 Diode lasers have shown antibacterial activity on dentinal tubules, they can penetrate more than 1000 μm into the dentin.…”
Section: Introductionmentioning
confidence: 99%
“…The photothermal effect of the lasers for microorganism destruction is used in the endodontic treatment [10]. The lower response rate of E. faecalis can be due to the greater durability of this heat microorganism [2,11]. In con-trast, Gutknecht et al (1996) [12] and Hardee et al (1994) [4] received 99% bacterial reduction in their studies.…”
Section: Discussionmentioning
confidence: 99%
“…The bactericidal effect of diode laser could be due to its greater penetration depth (1000 μm into dentinal tubules). [ 19 ] In addition, diode laser causes thermal photodisruptive action in inaccessible areas of dentin, overall resulting in an enhanced bactericidal effect. In the present study, the antibacterial action was significantly high against both aerobic and anaerobic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Its efficacy against diverse microorganisms has already been verified in various studies. [ 6 7 ] Another alternative that is currently being considered for disinfection of the root canal system is ozone therapy. The antimicrobial action of ozone is because of the lysis of dual bonds present on the cytoplasmic membranes of microorganisms.…”
Section: Introductionmentioning
confidence: 99%